Development of E-Comic Learning Media for Students in Grade IV of Xaverius 1 Elementary School Jambi - Benedikta Marsiana Putri; B.A Indriasari; Agnes Fibriana Kurniawati (Jurnal Evaluasi dan Pembelajaran, 2026)
This research aims to develop e-comic learning media that meets the criteria of validity, practicality, and effectiveness to enhance the learning motivation of 4th-grade elementary school students in IPAS subject, specifically concerning the heritage of the Sriwijaya Kingdom. The research method applied was Research and Development (R&D) using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects involved students across three stages: one-to-one, small group, and field test, with data collected through interviews, tests, and questionnaires. Validation results indicated that the media was highly feasible, with feasibility percentages of 92.5% for the media aspect, 90.83% for materials and questions, and 91.6% for language. Furthermore, trial results demonstrated a practicality level of 83.36% and an effectiveness rate of 85%, categorized as very effective. Based on these results, it can be concluded that the developed e-comic media is proven to be valid, practical, and effective for use in the learning process, also capable of enhancing students' motivation and understanding of historical material.